Exemplary Kyai and Santri's Morals in Pesantren: A Case Study of Pondok Pesantren Walisongo North Lampung - Dewi, Asmara; Ayu, Sovia Mas; Rahmadi, Tono; Muhammad Akmansyah (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2023)
Pesantren are traditional Islamic educational institutions that study, understand, explore, live, and practice the teachings of Islam by emphasizing the importance of religious morals as a guide to daily behavior. With the development of the times, technology and modernity are also developing along various lines, which causes the role of a santri to fade, especially in terms of akhlakul karimah in everyday life. This research seeks to analyze the application of exemplary methods in fostering Santri morals at Pesantren Walisongo in North Lampung, Indonesia. The research is field research. Data was obtained through observation, interviews, and documentation to complement research data in problem-solving. data analysis using the inductive thinking method. The population in this study was the caregiver of the Pesantren, the head of the Pesantren, the management, and all students of MA and MTs Plus Walisongo Lampung Utara, while the research sample was taken using the snowball sampling technique. The results of the study found that the application of the exemplary method implemented in the Pesantren Walisongo in North Lampung was effective. This was because it was not only exemplary in worship but consisted of several qudwah (exemplary), namely Qudwah Al-Ibadah, Qudwah Zuhud, Qudwah Tawadhu', Qudwah al Karimah, Qudwah Syaja'ah, Qudwah al Quwad al Jasadiyah, and Qudwah al Hasan al Siyasah